The Comparative Analysis of Caffeine in Fermented and Non-Fermented Arabica Coffee Beans - Romsiah; Pebyanti, Intan; Munarsih, Ensiwi; Hilma (Universitas Nusa Bangsa, 2025)
Arabica coffee is recognized as a high-value plantation commodity, favored for its distinctive flavor profile. However, its relatively high caffeine content can cause certain side effects in some individuals, such as sleep disturbances or increased blood pressure. One approach to reducing caffeine content without compromising flavor quality is fermentation using microorganisms. Rhizopus oryzae is known to produce enzymes capable of altering the chemical composition of coffee, making it a potential method for lowering caffeine levels while enhancing sensory quality. This study aimed to examine changes in physical properties and caffeine content of Arabica coffee powder subjected to fermentation with Rhizopus oryzae at concentrations of 1%, 2%, 3%, and 4% w/w, compared to a non-fermented control sample. The fermentation process was carried out for 24 hours at room temperature. Analyses included organoleptic evaluation, moisture content measurement, and caffeine determination using UV-Vis spectrophotometry. Results indicated that fermentation with Rhizopus oryzae at a 4% concentration yielded the most optimal outcome, with caffeine reduced to 0.95%, moisture content at 0.94%, and a final pH of 4.8. The brewed coffee from this treatment also exhibited a distinctive aroma, light brown color, and a balanced bitterness. Overall, fermentation with Rhizopus oryzae proved effective in reducing caffeine levels while maintaining and improving the sensory quality of Arabica coffee.